Pengaruh Kualitas Pelayanan Dan Keamanan Aplikasi Ebranch Bca Dan Kepuasan Nasabah Terhadap Loyalitas Nasabah Dengan Citra Perusahaan Sebagai Variabel Moderating Pada Pt Bank Central Asia Tbk., Kcu Tanjung Priok - Harris Manurung; Lani Diana Wijaya (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2020)
This study aims to examine the effect of Service Quality and Security of the eBranch BCA Application and Customer Satisfaction on Customer Loyalty and Corporate Image as moderating. The population in this study were customers of PT Bank Central Asia Tbk. who already have experience using the eBranch BCA application. The amount of data was 116 respondents who were taken through a questionnaire using partial least square (PLS) data analysis. Based on statistical tests, the results of the study show that the Service Quality and Security of the BCA eBranch Application and Customer Satisfaction have a significant effect on Customer Loyalty, Corporate Image has a significant effect on Customer Loyalty. Corporate Image Moderation has no significant effect and weakens the effect of Service Quality and Security of the BCA eBranch Application on Customer Loyalty. Corporate Image Moderation has insignificant effect and weakens the effect of Customer Satisfaction on Customer Loyalty Keywords : Service Quality, Application Security, Customer Satisfaction, Customer Loyalty, Corporate Image.